Barotropic instability over the Arabian Sea during the onset of summer monsoon 1979 (MAUSAM, 1985)
The daily low-level and upper-level satellite winds observed over the Arabian Sea in the domain 26°N-16°S and 4OoE-84°E are analyzed for the early stages of the summer monsoon in 1979. The wind analysis shows that before the onset of the monsoon over southern India, the low-level winds strengthen significantly, an onset vortex develops, and the low-level westerly jet shifts northward and broadens in the central Arabian Sea. A linear barotropic stability analysis of the zonal winds for the pre-onset, the vortex formation, the onset and the mature phases of monsoon flows is performed numerically for testing the hypothesis, that the onset vortex formation is primarily due to the Wave disturbances associated with baroscopic Instability In the mean zonal shear flow, and that the broadening of the low-level jet is partly due to dynamical consequence5 of the barotropic wave disturbances.